Créativité, dialogisme et multimodalité : trois qualités d’un environnement de conception numérique collaboratif - Frédérique Longuet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article focuses on the process of a collaborative learning device digitally enriched in initial teacher training. This experience is designed for the training of German student teachers at a master degree in the Paris Sorbonne school of education (ESPE Paris Sorbonne, 2014-2016). Our analysis reflects situated research, describes and interprets the dynamics of the participants. We have tried to find out, first of all, how the actors take over an unconstrained device, designed for this purpose. We have described this process according to three concepts, namely creativity, dialogism and multimodality. The situated microanalysis has led us to ask, in a second time, if the collaborative digital creation approach, we have followed, makes it possible to train creative teachers but also teachers aware of the institutional texts.